Application of recovery model for benefit of teachers - Nur Arifah, Amran; Puspa Liza, Ghazali; Fauzilah, Salleh; Nurul Zawani, Baharazi; Saffiah Aini, Ismail (2016)
Islamic insurance or takaful is commonly used by the people nowadays especially in most of the Muslim countries since it has been introduced. The system has evolved with many studies done to increase the effectiveness of the takaful application. However the existing model of takaful do not provide plan for the learning disabled children, even though their number is increasing year by year. The learning disabled children can recover with a consistent guidance and it may become a burden for the country, parents and special education teachers if something is not done to help them. Hence they need a special plan in takaful in recovery. This study discussed on the takaful education plan for the learning disabled children which will contribute much on their learning process of recovery. Using an integrated model of takaful education plan, a new recovery model of takaful education plan is proposed which consists plan that may assists the special education teachers in educating the learning disabled children.